2006
DOI: 10.1002/iroh.200610898
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Chemoautotrophic Production to Freshwater Macroinvertebrates in a Headwater Stream Using Multiple Stable Isotopes

Abstract: We estimated the food sources of macroinvertebrates using carbon, nitrogen, and sulfur stable isotopes in a headwater stream. Stream food webs, including macroinvertebrates, rely on production from autochthonous and allochthonous photosynthesis. We found that a freshwater grazer, the snail Semisulcospira libertina, may assimilate different food sources, based on stable carbon and nitrogen isotope evidence from snail muscle and the much lighter sulfur isotope signature than those of other associated macroinvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It’s been shown, for example, that the relatively low δ 13 C values from methanotrophic bacteria are detectable in midge larvae and other aquatic organisms that consume benthic detritus (Doi et al , 2006; Deines et al 2007), but this would not help explain 13 C enrichment in the mosquito larvae food web. Nadon & Himmelman (2006) have noted higher than expected enrichment of 13 C in primary consumers of marine benthic detritus (+ 4 δ 13 C).…”
Section: Discussionmentioning
confidence: 99%
“…It’s been shown, for example, that the relatively low δ 13 C values from methanotrophic bacteria are detectable in midge larvae and other aquatic organisms that consume benthic detritus (Doi et al , 2006; Deines et al 2007), but this would not help explain 13 C enrichment in the mosquito larvae food web. Nadon & Himmelman (2006) have noted higher than expected enrichment of 13 C in primary consumers of marine benthic detritus (+ 4 δ 13 C).…”
Section: Discussionmentioning
confidence: 99%
“…C and N stable isotope ratios have been increasingly used to analyze food web structures in aquatic ecosystems (e.g., Finlay 2001;Finlay et al 2002;Doi et al 2006;Delong and Thorp 2006). Stable isotope analysis should be a useful tool to estimate the contribution of drifting plankton to food webs.…”
Section: Introductionmentioning
confidence: 99%
“…In lacustrine ecosystems, food source diversity of benthic animals is poorly understood, although benthic invertebrate grazers are generally thought to feed on generalized mixtures of sediment detritus and microalgae (Reavell, 1980;Merritt & Cummins, 1996;Wetzel, 2001). However, recent studies have reported that chironomid larvae and snails feed on chemoautotrophic bacteria and vascular plants in addition to detritus and microalgae (Elger, Barrat-Segretain & Amoros, 2002;Grey, Kelly & Sleep, 2004;Doi et al, 2006a, Arakelova & Michel, 2009. The food sources of lymnaeid snails have been extensively studied because these snails are common in lakes and provide a large contribution to benthic and pelagic food webs (e.g.…”
Section: Introductionmentioning
confidence: 99%